NON-VERBAL COMMUNICATION IN HIGHER EDUCATION - Podkowińska, Monika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents the importance of non-verbal communication in the sphere of education at the level of higher education. In terms of the didactic process, education, two types of communication deserve special attention, i.e. public and interpersonal communication. The author presented the characteristics of the above types of communication situation and differences in the non-verbal feedback that are visible between the lecturer’s direct conversation with the student and the lecture given by the academic teacher. The article also indicates the types and functions of non-verbal behaviours, devoting particular attention to uses related to the use of proxemics in education. The significance of proxemics was characterised in the sphere of teaching, paying attention to issues concerning the feeling of congestion or maintaining distance relative to the communicative situation and goals between the academic teacher and a student. The factors determining the issues related to the feeling of congestion are also presented.